Experimental Study on High-Cycle Fatigue Behavior of GFRP-Steel Sleeve Composite Cross Arms - Jiantao Wang; Ning Tan; Shiming Zhou; Qing Sun (Advances in Civil Engineering)
To overcome the fatigue safety problem of transmission tower cross arms caused by the wind-induced vibrations, an experimental study on the high-cycle fatigue performance of a new type of GFRP-steel sleeve composite cross arms was carried out. A total of six specimens were subjected to 500 thousand cyclic loadings based on the practical engineering background. The stress state was monitored, and a variety of load-displacement-time curves, the energy dissipation capacity, and the dynamic strain were analyzed to examine the effects of fatigue loading. After the fatigue test, the specimens without significant fatigue failure were evaluated to derive the residual bearing capacity. Based on the residual strength theory, the cumulative damage was examined, and the fatigue life was predicted under various loading conditions to ensure the reliability of composite cross arms. It is shown that the new type full-scale GFRP-steel sleeve composite cross arms can demonstrate a high level of safety redundancy on antifatigue performance and can be expected for wide application in power transmission towers.